2009
DOI: 10.2165/00002018-200932010-00007
|View full text |Cite
|
Sign up to set email alerts
|

An Intervention to Improve Spontaneous Adverse Drug Reaction Reporting by Hospital Physicians

Abstract: A continuous intervention based on healthcare management agreements with economic incentives and educational activities is associated with a quantitative and qualitative improvement of spontaneous reporting of ADRs by hospital physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 23 publications
4
59
0
Order By: Relevance
“…But, only 5(2.3%) of those who diagnosed adverse drug reactions reported them to reporting centers. The considerable numbers of Nurses in the present study never reported an adverse drug reaction that is comparable with other studies (18)(19)(20).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…But, only 5(2.3%) of those who diagnosed adverse drug reactions reported them to reporting centers. The considerable numbers of Nurses in the present study never reported an adverse drug reaction that is comparable with other studies (18)(19)(20).…”
Section: Discussionsupporting
confidence: 91%
“…Results of a study performed in a tertiary teaching hospital in Barcelona/ Spain are similar to our study, and lack of time to report an adverse drug reaction due to the workload of clinical practitioners was detected as the most important reason to adverse drug reaction underreporting (19). Other causes of not reporting in that study were lack of information about the spontaneous reporting system, unavailability of yellow cards, doubt of adverse drug reaction causality assessment and lack of patient confidentiality (33).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Despite the positive and promising outcomes, the vast majority of these studies have been carried out with limited objectives and short follow-up periods. In addition, the majority of these studies was suffering from a limited number of participants, as they were mainly regional surveys and lacked the representation of all healthcare providers on the national level [9][10][11][12][13]. This leads us to raise an important question: Do healthcare professionals suffer from the problem of resistance to change and what are the possible strategies that could be adapted to mitigate this problem?…”
Section: Problem Backgroundmentioning
confidence: 99%
“…Several studies have shown that implementing simple strategies such as increasing the availability of more yellow cards in health centres, including a hyperlink to an online ADR reporting form in hospitals' electronic patient records, regular visits by a clinical expert, or educational measures as well as small financial incentives can increase the reporting of ADRs [36][37][38][39][40][41][42]. ADRs are still discovered by spontaneous reporting systems in hospitals, but electronic hospital information systems and the implementation of pharmacoepidemiological approaches increase the possibilities and the value of ADR detection in hospitals [17].…”
Section: Discussionmentioning
confidence: 99%